Therapeutic benefits of CD90‐negative cardiac stromal cells in rats with a 30‐day chronic infarct. Issue 3 (17th January 2018) - Shen, Deliang; Shen, Miaoda; Liang, Hongxia; Tang, Junnan; Wang, Bo; Liu, Chuang; Wang, Peiwen; Dong, Jianzeng; Li, Ling; Zhang, Jinying; Caranasos, Thomas G.
Abstract: Cardiac stromal cells (CSCs) can be derived from explant cultures, and a subgroup of these cells is viewed as cardiac mesenchymal stem cells due to their expression of CD90. Here, we sought to determine the therapeutic potential of CD90‐positive and CD90‐negative CSCs in a rat model of chronic myocardial infarction. We obtain CD90‐positive and CD90‐negative fractions of CSCs from rat myocardial tissue explant cultures by magnetically activated cell sorting. In vitro, CD90‐negative CSCs outperform CD90‐positive CSCs in tube formation and cardiomyocyte functional assays. In rats with a 30‐day infarct, injection of CD90‐negative CSCs augments cardiac function in the infarct in a way superior to that from CD90‐positive CSCs and unsorted CSCs. Histological analysis revealed that CD90‐negative CSCs increase vascularization in the infarct. Our results suggest that CD90‐negative CSCs could be a development candidate as a new cell therapy product for chronic myocardial infarction.